Q: How do you solve 2x minus 9x minus 4?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

2x2-9x+4 = (2x-1)(x-4) when factored

Assuming it's a plus sign, that factors to (2x + 1)(x + 4)

-4x-1-3x-4+5 = -7x-1-2x+1+6 -7x = -9x+6 2x = 6 x = 3

If you mean: 2x2 -9x +4 then it can be factored to (2x-1)(x-4)

2x squared minus 4

Related questions

2x2-9x+4 = (2x-1)(x-4) when factored

9x-4 = 7x+8 9x-7x = 8+4 2x = 12 x = 6

(3x - 4)(2x^2 + 6x + 5)

Assuming it's a plus sign, that factors to (2x + 1)(x + 4)

-4x-1-3x-4+5 = -7x-1-2x+1+6 -7x = -9x+6 2x = 6 x = 3

9x-5x-2x = -4 2x = -4 x = -2

(2x + 1)(x + 4) or (2x - 1)(x - 4) depending on the sign of the term in x and 4 being positive.

6 - 3x = 4 - 2x 6 = x + 4 x = 2 Check it. 6 - 6 = 4 - 4 It checks.

2x = 11x + 4 Subtract 11x from both sides: -9x = 4 Divide both sides by -9: x = 4/(-9) = -0.444...

1/4 = 3 - 2x - 1/ x + 24 ( 3 - 2x - 1 ) = 1 ( x + 2 )12 - 8x - 4 = x + 28 - 8x = x + 2-8x - x = 2 - 8-9x = -6x = -6/-9X = 2/3

If you mean: 2x2 -9x +4 then it can be factored to (2x-1)(x-4)

2x squared minus 4